(untitled) (Docentes 2.0 Journal, 2021)
Poor reading comprehension is one of the main problems faced by primary school teachers. In addition, it is one of the limiting factors in the academic performance of children in Colombia. This research analyzed the incidence of Aidan Chambers’ theory of literary conversation in strengthening reading comprehension in the third grade, Sede R Jagüi of Colegio Juan XXIII. The implemented methodology was based on the qualitative methodological paradigm, Action Research (IA), supported by a critical analysis with the active participation of the agents involved. The research was carried out with a group of two students. It was executed through the virtual teaching modality using the Zoom, WhatsApp, and Educaplay platform, through videos, album books, compositions, games, creations. The study was carried out with a sample of 2 third-grade students; their ages range between 8 and 9 years. It was proposed in the didactic unit of five work sessions to improve reading comprehension and address a series of themes about the territory. They made their productions to feed the final product (a web page) on the page. The proposal was effective, as can be seen from the results of the applied test in which it is possible to show the innovative strategies that allowed to improve the understanding of reading habits.